Economic conditions at the time of birth and cognitive abilities late in life: Evidence from eleven European countries - Gabriele Doblhammer; Gerard J. van den Berg; Thomas Fritze (Institute for the Study of Labor (IZA), 2011)
With ageing populations and a stronger reliance on individual financial decision-making concerning asset portfolios, retirement schemes, pensions and insurances, it becomes increasingly important to understand the determinants of cognitive ability among the elderly. Macro-economic recession and boom periods provide a unique opportunity to study the effect of changes in the early life economic environment on late life cognition. In European countries, about three to four economic recession and boom periods can be identified between 1900 and 1945. The timing of these periods differs between the countries, which makes a cross-country study design particularly powerful, as it is insensitive to country-specific confounding factors. We use data from the Survey of Health, Aging and Retirement in Europe (SHARE) among elderly individuals. This survey is homogeneous across countries. We use almost 20,000 respondents from 11 countries. We examine several domains of cognitive functioning at ages 60+ and link them to the macro-economic deviations in the year of birth, controlling for current demographic, socioeconomic and health status. We find that being born during a recession or boom period significantly influences cognitive functioning late in life in various domains. The effects are particularly pronounced among the less educated. Boom periods positively influence numeracy and verbal fluency as well as the score on the omnibus cognitive indicator. The results are robust; controlling for current characteristics does not change effect sizes and significance. We conclude that cognitive functioning late in life is influenced by economic conditions in the year of birth, and we discuss possible causal pathways.
urn:nbn:de:101:1-201109286335
Keywords: I12; I18; J14; N14; N34; J26; 330; cognition; economic business cycle; developmental origins; health; long-run effects; dementia; numeracy; memory; decision-making; Lebensverlauf; Wirtschaftslage; Kognition; Gesundheitsrisiko; EU-Staaten